2016
DOI: 10.1186/s12872-016-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

A potential marker of bare metal stent restenosis: monocyte count - to- HDL cholesterol ratio

Abstract: BackgroundOxidation and inflammation play significant roles in the pathogenesis of coronary artery diseases. Monocyte count to high-density lipoprotein (HDL) cholesterol ratio (MHR) is a new marker and has revealed as an indicator of inflammation in the literature. The present study aimed to search the effect of MHR on in-stent restenosis (ISR) in patients with stable or unstable angina pectoris undergoing bare-metal stent (BMS) implantation.MethodsA total of 468 consecutive stable or unstable angina pectoris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…In another study, in patients with acute ST-segment elevation myocardial infarction (STEMI), MHR values at admission were independently correlated with in-hospital adverse cardiovascular events and stent thrombosis and mortality [31]. In two different studies MHR values were found to be in relation with in-stent restenosis [32,33]; also MHR was found to be correlated with presence and severity of ectasia [13].…”
Section: Discussionmentioning
confidence: 98%
“…In another study, in patients with acute ST-segment elevation myocardial infarction (STEMI), MHR values at admission were independently correlated with in-hospital adverse cardiovascular events and stent thrombosis and mortality [31]. In two different studies MHR values were found to be in relation with in-stent restenosis [32,33]; also MHR was found to be correlated with presence and severity of ectasia [13].…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the preprocedural values of MHR and CRP levels were higher in in-stent restenosis than non-in-stent restenosis patients with stable or unstable angina pectoris after bare-metal stent implantation and MHR (HR, 1.09; 95% CI, 1.04-1.14). The latter was an independent predictor of in-stent restenosis in addition to high CRP and uric acid (a marker of oxidative stress; Ucar, 2016).…”
mentioning
confidence: 99%
“…MHR is investigated as a novel inflammatory marker and suggested to be superior to WBC subtypes in patients with cardiovascular and cerebrovascular diseases (19,20). Monocytes are inflammatory reaction markers responsible of release of proinflammatory and prooxidant cytokins (21).…”
Section: Discussionmentioning
confidence: 99%